2019
DOI: 10.1002/open.201900135
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Chain Transfer Copolymerization of Propylene Oxide and CO2 using Zinc Glutarate Catalyst

Abstract: Oligo and poly(propylene ether carbonate)‐polyols with molecular weights from 0.8 to over 50 kg/mol and with 60–92 mol % carbonate linkages were synthesized by chain transfer copolymerization of carbon dioxide (CO 2 ) and propylene oxide (PO) mediated by zinc glutarate. Online ‐monitoring of the polymerization revealed that the CTA controlled copolymerization has an induction time which is resulting from reversible catalyst deactivation by the CTA. Latter is neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 120 publications
(170 reference statements)
0
12
0
Order By: Relevance
“…No apparent change is seen of the molecular weight distri-bution (Đ) (Table 2), most probably because the chain exchange reaction occurs rapidly relative to the propagation reaction. 21 Moreover, under the studied copolymerization conditions, the CU linkage in the resultant polyols was in the range of 36.9-44.0%, and W cPC was less than 3.0% (Table 2). It was also found that the reaction time was shortened by more than 3 times from 8.0 h to 2. a Copolymerization conditions: T = 95 °C, P CO2 = 4 MPa, catalyst = 15 mg, and PO = 50 mL (0.72 mol).…”
Section: Papermentioning
confidence: 93%
See 1 more Smart Citation
“…No apparent change is seen of the molecular weight distri-bution (Đ) (Table 2), most probably because the chain exchange reaction occurs rapidly relative to the propagation reaction. 21 Moreover, under the studied copolymerization conditions, the CU linkage in the resultant polyols was in the range of 36.9-44.0%, and W cPC was less than 3.0% (Table 2). It was also found that the reaction time was shortened by more than 3 times from 8.0 h to 2. a Copolymerization conditions: T = 95 °C, P CO2 = 4 MPa, catalyst = 15 mg, and PO = 50 mL (0.72 mol).…”
Section: Papermentioning
confidence: 93%
“…6,7,[9][10][11][12][13][14][15][16][17] Most of the reported works have been focused on linear oligo(carbonate-ether) diol polymers. [18][19][20][21][22][23][24] However, the bifunctional linear structure usually makes it difficult to construct rigid and soft crosslinked PU foams.…”
Section: Introductionmentioning
confidence: 99%
“…Care is taken to keep the heat content of the reaction mixture below the reactors' safety limits; it always needs to be assured that the catalyst has been activated and PO is consumed before additional feeding of PO, e.g., to get to higher molecular weights. The products of this study all are liquids-the thermal properties [68] follow the Flory-Fox equation-and are dependent on the molecular weight and the composition. The timeline of a typical copolymerization experiment ( Figure 1c) thus comprises (i) a drying procedure at 120 • C, (ii) the initiation by catalyst activation (in the presence of PO and argon respectively CO 2 ), (iii) for copolymerization, adjustment of CO 2 pressure and temperature to the desired value and addition of PO in batch or semi-batch mode.…”
Section: Homopolymerization Of Po and Copolymerization With Co 2 In Bmentioning
confidence: 99%
“…DDA does not show any effect on the induction time or conversion of batch PO. This may be related to either the low coordination strength or the fact that DDA can react with PO to generate a further CTA of low coordination strength [68]. The copolymer composition seems to be largely unaffected by the presence of TEA or DDA at N = 0.115 and at 120 • C. The carbonate content is still in the range of 14 mol% (Table 8, Entry 35-39 and 45-48).…”
Section: Amines As Cocatalyst/conucleophilementioning
confidence: 99%
See 1 more Smart Citation